Creation of the Construction of the Digger-Loader with a Centrifugal Separation - Gulamovich, Bayboboev Nabijon (International Journal of Psychosocial Rehabilitation, 2020)
Qualitative performance indicators of potato harvesters largely depends on the design of the separating working bodies. In this regard, the purpose of this article is to create a centrifugal lifting separating working body of a potato-harvesting machine, which ensures the effective separation of potato tubers from the soil with centrifugal forces. Therefore, it was proposed to modernize the separating working bodies of the potato harvester, namely, to use an elevator with a centrifugal separation and a clamping device with flanges in the potato harvester, this device is new in that the flanges are made in the form of separate sectional elements and installed with the possibility of radial change of position. This design of the separating working body to provide increased productivity, expanding technical capabilities and reducing the energy intensity of the process.